Acute acalculous cholecystitis causing gall bladder perforation in children - Karkera Parag; Sandlas Gursev; Ranjan Ritesh; Gupta Abhaya; Kothari Paras (Wolters Kluwer Medknow Publications, 2010)
We report two cases of children who presented with acute abdomen due to gall bladder perforation and biliary peritonitis. Cholecystectomy with peritoneal lavage proved curative.